Kepraktisan Penggunaan CD Multimedia Interaktif pada Mata Kuliah Draping Tata Busana Fakultas Teknik Universitas Negeri Makassar - Siti Aisyah; Srikandi Srikandi; Fatmawati Fatmawati (Seminar Nasional LP2M UNM, 2019)
This study aims to determine the practicality of the use of interactive multimedia CD that are viewed in terms of effective, efficient, creative, interactive and interesting that are used in the Draping at Fashion Study Program, Faculty of Engineering, Universitas Negeri Makassar. This type of research is quantitative research with descriptive data analysis. The subjects were 25 students. The results showed the practicality of interactive multimedia CD in the learning process of draping to meet the requirements based on the requirements of the practicality requirements of the media or teaching materials used in the learning process.